2007
DOI: 10.1002/pd.1834
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome topology in normal and aneuploid blastomeres from human embryos

Abstract: Peripheral localization of chromosome 18 in aneuploid blastomeres is related to embryo aneuploidy. Conversely, a peripheral localization of the inactive X chromosome was not found in blastomeres from 3-4 day old embryos. These results open the possibility to improve embryo selection after pre-implantation diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, as demonstrated by the goodness of fit test, aneuploidies were not randomly distributed within the same oocyte, suggesting that aneuploidies are probably caused by a dysfunction of the meiotic spindle rather than by the shape and features of the chromosomes. The physiological implications of this condition are unknown but other studies in sperm cells and in preimplantation embryos have reported that chromosomes have a defined, non-random localization within the nucleus, suggesting that the organization of the genome could be functionally important (Foster et al ., 2005; Mudrak et al ., 2005; Diblik et al ., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as demonstrated by the goodness of fit test, aneuploidies were not randomly distributed within the same oocyte, suggesting that aneuploidies are probably caused by a dysfunction of the meiotic spindle rather than by the shape and features of the chromosomes. The physiological implications of this condition are unknown but other studies in sperm cells and in preimplantation embryos have reported that chromosomes have a defined, non-random localization within the nucleus, suggesting that the organization of the genome could be functionally important (Foster et al ., 2005; Mudrak et al ., 2005; Diblik et al ., 2007). …”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only three previous studies on nuclear organisation in human embryos: two of the three (Diblik et al 2007;McKenzie et al 2004) showed no evidence of a chromocentre, whereas the other study (Finch et al 2008a) indicated its presence. The dynamics of nuclear organisation and its relationship to gene expression in the early human embryo clearly warrant further investigation, in particular if there are patterns that may indicate future development potential.…”
Section: Discussionmentioning
confidence: 82%